The country-of-origin lie: impact of foreign branding on customers' willingness to buy and willingness to pay when the product's actual origin is disclosed. Issue 1 (1st January 2017) - Aichner, Thomas; Forza, Cipriano; Trentin, Alessio
Abstract: If you think about the last television commercial for an Italian pasta brand you have seen, are you sure it is really Italian? In many cases, especially in the food sector, neither the company nor the product originate from the advertised country, meaning that the company is pursuing a foreign branding strategy and is trying to benefit from positive stereotypes customers have about the specific foreign country. By collecting both quantitative and qualitative data through a point-of-sale intercept survey, this article assesses the impact of alleged origins on customers' willingness to buy (WTB) and willingness to pay (WTP) if the actual origin is disclosed. The sample consisted of 200 German customers who were asked to answer questions related to one of two hedonic products they had just bought. It is empirically shown that foreign branding has a positive impact on the brand's performance. However, as soon as customers find out that they were misled with regard to the origin of the product, both their WTB and their WTP decrease. This study contributes to the knowledge on the role of products' origins on customers' WTB and WTP. In contrast to the vast majority of the studies in this field, the communicated origin of the product is based on a foreign branding strategy and not on the product's actual origin. Consequently, it was possible to manipulate within-subject variables by disclosing the actual origin of the product. The results of our study suggest that foreign branding may be a successful strategy for companies to increase their customers' WTB and WTP. At the same time, our results raise concerns about the suitability of foreign branding as a long-term marketing strategy, unless a company can successfully maintain its foreign image. Future research opportunities include the choice of consumers with a different cultural background, of other hedonic products or of utilitarian products.